Relationship between Antidepressant Use and Increased Bacterial Resistance (Global Journal of Medical Research, 2023)
The uncontrolled use of antidepressant drugs can be potentially harmful to individual and collective health. Analgesics are often used inappropriately and carelessly, which can result in a number of negative effects like bacterial resistance, hypersensitivity, dependence, digestive bleeding, withdrawal symptoms, and even an increased risk for certain neoplasms (Ribeiro et al., 2010). The central nervous system, as well as the respiratory and digestive systems, are the sources of the complaints that are most frequently linked to self-medication, including headache, musculoskeletal pain, fever, respiratory infections, heartburn, abdominal pain, constipation, and diarrhea (Furtado et al., 2019).
Keywords: antidepressants; bacterial resistance; drug interaction